Hypoplastic left heart syndrome with prenatally diagnosed foramen ovale restriction: diagnosis, management and outcome. (17th January 2022) - Jadczak, Anna; Respondek-Liberska, Maria; Sokołowski, Łukasz; Chrzanowski, Jędrzej; Rizzo, Giuseppe; Araujo Júnior, Edward; Bravo-Valenzuela, Nathalie Jeanne; Axt-Fliedner, Roland; Słodki, Maciej; ,
Abstract: Objective: Despite advances in prenatal diagnosis and postnatal intervention/surgery methods, patients with Hypoplastic Left Heart Syndrome (HLHS) and coexisting foramen oval restriction still achieve high mortality rates. Our objective was to determine survival predictors and to find answers to, why restriction develops in some, but not others. Methods: We performed a retrospective analysis of prenatal history and postnatal sequel of 22 patients with HLHS and foramen ovale restriction between 2008 and 2017. Results: There were 11 survivors and 11 nonsurvivors. The most significant difference between the two groups pertained to the average time of foramen ovale restriction diagnosis which was 33 weeks for survivors and 28 weeks for nonsurvivors ( p  = .0416) and the duration of in-utero restriction (9 versus 5 weeks, p  = .0213). Twenty patients (20/22) exhibited possible signs of infection. Conclusions: (1) Earlier development and longer presence of foramen ovale restriction in the setting of HLHS is associated with higher short-term mortality regardless of the degree of restriction. (2) Ratio of forward pulmonary vein flow to reverse flow ( f / r ) expressed as a velocity-time integral (VTI) is a good emergent intervention predictor, but it does not correlate with foramen ovale size and maximal velocity, nor does it influence survival rates. (3) Ultrasonographic signs of possible infection of the fetus is a potential risk factor of foramen ovale restriction development in patients with HLHS.